Anti-Tumor Necrosis Factor Blocking Agents in the Treatment of Systemic Vasculitis - Qubti, Marzouq; Seo, Philip (Current Immunology Reviews (Discontinued), 2011)
The primary systemic vasculitides are idiopathic disorders characterized by the inflammatory destruction of blood vessel walls. Many of these disorders are treated with high-dose glucocorticoids and cytotoxic agents which, while effective, are associated with substantial morbidity, particularly for patients who experience recurrent flares requiring chronic therapy. Therefore, attention has turned towards biologic therapies that abrogate specific elements in the inflammatory cascade. Tumor necrosis factor-α is a cytokine that is central to systemic inflammation in many diseases. This article will review the role played by tumor necrosis factor-α in the pathogenesis of systemic vasculitis, and attempt to define a role for blockade of tumor necrosis factor-α in the treatment of patients with these diseases.
Keywords: inflammation